2004
DOI: 10.1039/b402370f
|View full text |Cite
|
Sign up to set email alerts
|

The role of surface electrification on the growth and structural features of titania nanoparticles

Abstract: TiO 2 particles, prepared by following a sol-gel preparative route, were submitted to hydrothermal steps performed at solution pH values corresponding, respectively, to positive, zero and negative oxide surface charges. After the hydrothermal step all the samples were thermally treated at 300 and 600 C, for the same length of time (6 h). The powders, both precursors and calcined samples, were characterized for phase composition-crystallinity, particle morphology and surface electrification features. The role p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…The conditions of the solgel reaction (water/alkoxide and water/alcohol ratios) were selected such as to promote the formation of materials with reduced crystallite sizes, after the calcination [24,25]. Fig.…”
Section: Structural and Morphological Featuresmentioning
confidence: 99%
“…The conditions of the solgel reaction (water/alkoxide and water/alcohol ratios) were selected such as to promote the formation of materials with reduced crystallite sizes, after the calcination [24,25]. Fig.…”
Section: Structural and Morphological Featuresmentioning
confidence: 99%
“…Thus synthetic methods for both particles and layers should be developed in which the crystalline form as well as the size, shape and texture of the TiO 2 nanocrystals can be controlled [18,19]. This article focuses on the synthesis of tailored TiO 2 powders [20][21][22] and layers (deposited onto Ti and Au supports) through a simple process implying a sol-gel starting reaction, followed by a growth step in solution and a final calcination at low temperature (300°C). The particles and layers are subjected to morphological (BET, SEM) and structural characterizations (XRD).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, low synthesis temperature is a significant advantage for device applications since it enables the use of flexible plastic substrates and easy integration with organic optoelectronic device fabrication. It was shown that the morphology of the obtained ZnO [12], indium tin oxide [13], titania [14], and yttria [15] nanostructures by solution-phase growth strongly depends on the pH value of the solution. The surface electrification of an oxide depends on the solution pH.…”
Section: Introductionmentioning
confidence: 99%
“…Decreasing the pH will lead to adsorption of protons, while increasing the pH will lead to the absorption of hydroxyl ions [16]. The presence of surface charges will affect the aggregation and ripening of the nanostructures [14]. The aggregation of the nanostructures is dependent on the presence or absence of electrostatic repulsion, while the negative surface charge may hinder Oswald ripening process [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation